Obtaining source current density related to irregularly structured electromagnetic target field inside human body using hybrid inverse/FDTD method. (3rd April 2017) - Han, Jijun; Yang, Deqiang; Sun, Houjun; Xin, Sherman Xuegang
ABSTRACT: Inverse method is inherently suitable for calculating the distribution of source current density related with an irregularly structured electromagnetic target field. However, the present form of inverse method cannot calculate complex field–tissue interactions. A novel hybrid inverse/finite-difference time domain (FDTD) method that can calculate the complex field–tissue interactions for the inverse design of source current density related with an irregularly structured electromagnetic target field is proposed. A Huygens' equivalent surface is established as a bridge to combine the inverse and FDTD method. Distribution of the radiofrequency (RF) magnetic field on the Huygens' equivalent surface is obtained using the FDTD method by considering the complex field–tissue interactions within the human body model. The obtained magnetic field distributed on the Huygens' equivalent surface is regarded as the next target. The current density on the designated source surface is derived using the inverse method. The homogeneity of target magnetic field and specific energy absorption rate are calculated to verify the proposed method.